Euforia y pesimismo en tiempos de internet. Hacia una relectura de los efectos políticos de los medios sociales a la luz de las mediaciones - Makedonski Valdeavellano, Paul Maquet (2020)
The article seeks to situate the contemporary debate around the supposed effects of the Internet and social media on politics, in light of the longstanding discussion about media effects. In this line, it draws attention to the persistence of a certain «technical ideology» that presumes a capacity of technologies to directly and decisively influence political and social transformations, to highlight a political debate around institutional and economic mediations, social uses, and cultural mediations in the development of these media.